The Concept of Environmental Security in International Relations: Definition, Features, Implications - ZAPOLSKIS, MARTYNAS (Politologija, 2012)
[full article and abstract in Lithuanian; abstract in English] This article examines the concept of environmental security and assesses its role in international, regional and national security studies. The study is aimed at providing conceptual „mental map“ of this field, thereby giving analytical background and guidance for comprehensive environmental security studies, which are known for the diversity of conceptual approaches, methods and levels of analysis. The fundamental question of environmental security – how various environmental factors (climate, resources, etc.) and processes can affect the security of states and societies. It examines the relationships between different environmental issues, their effects and various security problems. Environment is considered as integrated part of a security concept together with the dimensions of economic, social, energy or information security. In order to identify the main academic schools of the environmental security, this article uses four key questions, theoretically defining the core of environmental security concept: (i) what makes an impact (source of threat); (ii) to whom/what an impact is made („victim”); (iii) what kind of impact is made (threat); (iv) how an impact is made (mechanisms and “channels”). On the basis of these theoretical dimensions, five main academic schools of environmental security are identified and examined by focusing on their features and findings, methodology and critical assessment: 1. Resource scarcity school examines the nexus between scarcity of renewable resources (e.g. freshwater) and various internal and international conflicts (their incidence, intensity and dynamics). 2. Resource abundance school explores the relations between non-renewable resources (e.g. diamonds, oil, etc.) and internal conflicts, especially civil wars. 3. Climate change school focuses on nature (and human) induced environmental change and its implications for international security, socioeconomic development and social disruptions in various regions. 4. Human security school focuses on environmental impacts on individual and “people-centered” security, which is closely related with sustainable development (food security, health and education, welfare, gender issues, etc.). 5. Natural disasters school examines the socioeconomic impacts of various disasters (earthquakes, floods, etc.) with specific focus on the vulnerability and adaptive capacity of various social systems (states, communities, etc.). Analysis shows that environmental dimension becomes increasingly important element of international relations and security studies. Comprehensive security assessment, especially in developing countries, is not possible without taking into account the social and economic impacts made by resources, climate change and natural disasters. Research by 1 and 2 schools, despite various methodological problems, demonstrates the impact resources have to various internal conflicts and social disorder. Scarcity of renewable resources generates certain social effects (for example, decreased productivity of agriculture, migration, weakening of state institutions etc.), which, in turn, can fuel different types of conflicts (ethnic conflicts, coup d’état, poverty conflicts, etc.). Abundance of non-renewable resources can have various direct (for example, direct financial source for rebel groups), as well as indirect (affecting economy, political regime, separatism, etc.) impact to conflicts. Specific conditions in the developing countries play a significant role in terms of explaining the nexus between resources and security. Developing countries are often dependent on climate-sensitive agriculture and suffer from poverty. As a result, various climate change effects (3 school) often amplify mechanisms, which lead to insecurity and violence, such as political instability, weak governance structures, poor economic performance, etc. This is especially relevant for those regions where several “conflict constellations” (water and food shortage, regular natural disasters, rapid demographic change, etc.) are overlapping. Environmental change also has a certain impact to international security in terms of possible increase in the number of weak and fragile states, risks for global economic development, intensification of migration, territorial disputes, etc. Generally, environmental security research (apart from the 1 and 2 schools) is based on a broad approach to security, which is not limited to military conflicts and include various elements of sustainable development and economic welfare. On the one hand, it is understandable, as interdisciplinary character of environmental security requires complex approach to security. On the other hand, research based on the concept of human security (4 school) often equates security with economic and social well-being, thus blurring the line between security and development studies. It also undermines the assessment of the impact environmental issues can have to traditional security problems (conflicts, regime change, political instability, etc.). Finally, securization of various social problems (AIDS, migration, poverty, gender inequality, etc.) might be used for political purposes by legitimizing the use of military force or restricting human rights. Various natural disasters (5 school) have a substantial destructive power, which not only causes substantial damage (humanitarian crises, destroyed infrastructure, etc.), but also has complex socioeconomic and political effects, which affect political regimes, critical economic sectors, social stability, etc. From this perspective, a key role is played by physical and socioeconomic characteristics of vulnerability and adaptive capacity, which can absorb negative effects of natural disasters and mitigate the risk.